Economic Value of Ecosystem Restoration in Biscayne Bay, Florida - Donna J. Lee; Anafrida Bwenge (EDIS, 2006)
FE662, a 5-page fact sheet by Donna J. Lee and Anafrida Bwenge, describes a study which assesses the value of restoring ecosystems damaged by invasive plants. Includes references. Published by the UF Department of Food and Resource Economics, August 2006.